-4x+6=3x+-8

Simple and best practice solution for -4x+6=3x+-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+6=3x+-8 equation:


Simplifying
-4x + 6 = 3x + -8

Reorder the terms:
6 + -4x = 3x + -8

Reorder the terms:
6 + -4x = -8 + 3x

Solving
6 + -4x = -8 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
6 + -4x + -3x = -8 + 3x + -3x

Combine like terms: -4x + -3x = -7x
6 + -7x = -8 + 3x + -3x

Combine like terms: 3x + -3x = 0
6 + -7x = -8 + 0
6 + -7x = -8

Add '-6' to each side of the equation.
6 + -6 + -7x = -8 + -6

Combine like terms: 6 + -6 = 0
0 + -7x = -8 + -6
-7x = -8 + -6

Combine like terms: -8 + -6 = -14
-7x = -14

Divide each side by '-7'.
x = 2

Simplifying
x = 2

See similar equations:

| 1000/9.81 | | 52-3x=24x+16 | | 1+x^4-2x^2+1.96x^2=1.0096x^4 | | -6x+7=10-5x | | 60+.6x=.8x | | (w+8)(w-3)=0 | | 60+.6=.2 | | 5x+10=64-4x | | 5y^2+9=3y | | y^2=6y+7 | | 6x+13=35-3x | | (3d+2)(7-1)=0 | | -4x-10=46+5x | | (1/3x)=9 | | 4x+1=60 | | 5x-16=4x+5 | | x-10=-21+2x | | x^2=5+4x | | x+7=-0 | | 5+7=3x | | x^2=y^4-77 | | y=5-8x | | 12x-10=4x-5 | | 2x+3=33+7x | | (-3y^2-8y)+(6y^2+y-9)= | | 18(4/9) | | -4/7+2/5u=-1/2 | | -4+7x=x+20 | | 9x+6=3x-2 | | 5(8)+8y=40 | | x*x+6x+c= | | 6y^2+11=4y |

Equations solver categories